Accident Rate of Different Types of Gliders in the Czech Republic - Hůlek, David; Novák, Martin; Řeha, David; Němec, Vladimír (Kaunas University of Technology, 2022)
This article deals with the accident rate of gliders during the last decade in the Czech Republic. Gliding has a solid base in the Czech Republic and an analysis of their accident rate according to the glider type may benefit future research in this area. The first part of the paper explains the data sources of the accident rate calculations and their evaluation. It describes the different glider types that were analysed and provides a list of their most common use. The next part of the article is about a calculation of the accident rate for each glider type and their evaluation. The last section of this article presents a summary of the findings and the main conclusions from the data analysis.
Nehodovost jednotlivých typů kluzáků na území České republiky
Keywords: air accident; accident rate; glider; glider accidents; gliders in the Czech Republic; air accidents in the Czech Republic; letecká nehoda; nehodovost; kluzák; nehody kluzáků; kluzáky v České republice; letecké nehody v České republice